2019
DOI: 10.1155/2019/9848125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypertension Duration and the Age of Onset on CV Risk Factors Expression in Perimenopausal Women

Abstract: Background The impact of hypertension duration and the time of onset on the expression of metabolic syndrome (MS) and other CV risk factors, in perimenopausal women, have not been studied so far. Methods. A total of 202 women, old 47–59 years, and diagnosed with hypertension, were recruited from primary care practices in eastern Croatia. The categories of hypertension duration were defined as <5, 5–10, and >10 years. Data were analyzed by standard statistical procedures. Results The proportion of women with MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
5
0
3
Order By: Relevance
“…These changes in the female CV risk profile, after the age of 50 (the average age of menopause), are difficult to distinguish from age-related changes in CV risk factors [ 14 ]. Changes in body shape and composition, which occur with aging, including loss of muscle mass and increase in fat tissue, in particular visceral fat tissue, may exaggerate inflammatory response and induce peripheral tissue resistance to insulin, predisposing older individuals to metabolic disorders, hypertension, and the development of the structural changes of the CV system [ 15 , 16 ].…”
Section: Proposed Underlying Mechanisms Of Differences Between Men and Women In Cardiovascular Disease Patternsmentioning
confidence: 99%
“…These changes in the female CV risk profile, after the age of 50 (the average age of menopause), are difficult to distinguish from age-related changes in CV risk factors [ 14 ]. Changes in body shape and composition, which occur with aging, including loss of muscle mass and increase in fat tissue, in particular visceral fat tissue, may exaggerate inflammatory response and induce peripheral tissue resistance to insulin, predisposing older individuals to metabolic disorders, hypertension, and the development of the structural changes of the CV system [ 15 , 16 ].…”
Section: Proposed Underlying Mechanisms Of Differences Between Men and Women In Cardiovascular Disease Patternsmentioning
confidence: 99%
“…In this study it was also found that the duration of hypertension increased the risk of developing metabolic syndrome. [22], [23] The metabolic syndrome (hypertension and type 2 diabetes) with a family history of chronic disease so it can be said that there is a significant relationship between the metabolic syndrome (hypertension and type 2 diabetes mellitus) and a family history of chronic disease. Which states that family history is one of the parameters incorporated in several genetic substances including perisoxome proliferators, CD3C adiponectin, Badrenergic receptors, insulin substrate receptors, Bdihydroxylated dehydrogenases, and adipocytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to identify the patterns of inflammatory markers that are involved in certain clinical contexts, determined by age and gender of patients with DM2 and including also information on DM2 and hypertension duration and the time of onset, as the core framework for determining these patterns. By keeping in mind that the scored values of markers of inflammation stay in a balance with the net effect of disorders that can influence their values, phenotypes indicated by the clusters provided insights into the phases of inflammatory responses that are involved in strictly defined clinical frameworks, thus being reflective of the dynamics of developing DM2-associated comorbidities [ 3 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, sex dimorphism may have influenced the distribution of comorbidities in the clusters. Specifically, in women, as we emphasized in our previous studies, the transition from pre- to postmenopause and the early postmenopausal period are critical periods in women’s lives when CV risk factors are significantly modified, which specifically in women can add to the diversity of DM2-related phenotypes [ 44 , 68 ]. Some other studies have also provided important insights into the reasons for the heterogeneity of older patients with DM2, indicating factors such as the current patient age and DM2 duration and age of onset [ 41 ].…”
Section: Discussionmentioning
confidence: 99%